Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.2527/1995.7351493x
|View full text |Cite
|
Sign up to set email alerts
|

Pasture management strategies for reducing the risk of legume bloat in cattle

Abstract: Results from two decades (1973-1993) of bloat research at Kamloops are reviewed. The trials were conducted with groups of ruminally fistulated cattle either grazing or fed daily fresh-cut alfalfa (Medicago sativa) herbage. Studies were conducted during the growing season (May to September) and in the fall (October and November). The alfalfa was usually in the vegetative to early bloom stages of growth. Visual assessments of bloat severity on a scale of 1 to 5 were made .5 to 2 h after feeding started, at which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0
7

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 28 publications
2
84
0
7
Order By: Relevance
“…This increased performance was a result both of a greater energy intake and a 14% higher efficiency in this phase, which agrees with other studies comparing restricted-realimented v. continuously grown animals (Ellenberger et al, 1989;Hornick et al, 2000). The low incidence of bloat in this study is in accordance with the review of Majak et al (1995), who concluded that the risk of bloat was low when cattle grazed on lucerne continuously.…”
Section: Discussionsupporting
confidence: 92%
“…This increased performance was a result both of a greater energy intake and a 14% higher efficiency in this phase, which agrees with other studies comparing restricted-realimented v. continuously grown animals (Ellenberger et al, 1989;Hornick et al, 2000). The low incidence of bloat in this study is in accordance with the review of Majak et al (1995), who concluded that the risk of bloat was low when cattle grazed on lucerne continuously.…”
Section: Discussionsupporting
confidence: 92%
“…Ruminally fistulated 5-to 8-yr-old Jersey steers were confined in groups (usually with four steers per pen) and were fed fresh alfalfa herbage, with and without sainfoin, at 08:00 h daily. Ruminal cannulae of all steers were opened at least once daily, approximately 1.5 h after feeding, for assessment of severity of bloat as described by Majak et al (1995). One or more occurrences of bloat scoring 3 or higher in the same steer on a given day were recorded as a single animal-day of bloat.…”
Section: Animal Feeding Trials -Bloat Occurrencementioning
confidence: 99%
“…When necessary, ruminal venting was used to relieve ruminal distension and/or distress in steers exhibiting multiple bloats on a given day. Crossover periods were continued until at least 24 incidents of bloat were observed (Majak et al 1995). Comparisons of the effects of sainfoin on the occurrence of bloat were made using Cochran's Q test (Cochran 1950).…”
Section: Animal Feeding Trials -Bloat Occurrencementioning
confidence: 99%
“…It should be noted that unlike continuous grazing, feeding in confinement is a much more vigorous test of a treatment owing to the higher incidence of bloat (Majak et al 2001). The length of each period of the crossover trial continued until the sum of the cases of bloat reached a minimum of 24 (Majak et al 1995). Between periods, cattle were fed alfalfa hay for at least 1 d. Animals were cared for under the guidelines of the Canadian Council on Animal Care.…”
mentioning
confidence: 99%
“…Ruminal cannulae of all steers were opened at least once daily beginning approximately 0.75 to 2.0 h after feeding began, to assess the severity of bloat as described by Majak et al (1995). The average feeding time was approximately 6 h head…”
mentioning
confidence: 99%